2018
DOI: 10.1371/journal.pone.0194882
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of red-blood cell fatty acids and ratios incorporating dietary covariates: Framingham Heart Study Offspring Cohort

Abstract: Recent analyses have suggested a strong heritable component to circulating fatty acid (FA) levels; however, only a limited number of genes have been identified which associate with FA levels. In order to expand upon a previous genome wide association study done on participants in the Framingham Heart Study Offspring Cohort and FA levels, we used data from 2,400 of these individuals for whom red blood cell FA profiles, dietary information and genotypes are available, and then conducted a genome-wide evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…The post-hoc covariate adjustment on both individual fatty acids and PCA for the Omega-3 and Omega-6 fatty acids hit genes that have been found in previous GWAS on fatty acids such as FADS1, ELOVL2, and LPCAT3. 1921 Using principal components and covariate adjustment we found a novel gene that has not yet been found associated with fatty acids before: PTPRM, and another (AGPAT4) that was only identified with a fatty acid ratio before on this sample. 19 Table 2 displays all SNPs found significant with any individual Omega-3 or Omega-6 fatty acid, or the first, second, or third principal components of either Omega-3 or Omega-6 fatty acids.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The post-hoc covariate adjustment on both individual fatty acids and PCA for the Omega-3 and Omega-6 fatty acids hit genes that have been found in previous GWAS on fatty acids such as FADS1, ELOVL2, and LPCAT3. 1921 Using principal components and covariate adjustment we found a novel gene that has not yet been found associated with fatty acids before: PTPRM, and another (AGPAT4) that was only identified with a fatty acid ratio before on this sample. 19 Table 2 displays all SNPs found significant with any individual Omega-3 or Omega-6 fatty acid, or the first, second, or third principal components of either Omega-3 or Omega-6 fatty acids.…”
Section: Resultsmentioning
confidence: 87%
“…Previous genome wide association studies explored associations between SNPs and red blood cell fatty acid (RBC FA) levels indicative of various health measures such as cardiovascular health and inflammation using data from The Framingham Heart Study. 1921 We applied our method to unrelated individuals in the Generation 3 and Offspring cohorts with a sample size of 1,454 with data on 408,595 SNPs after quality control. We investigated the Omega-3 and Omega-6 fatty acids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strong genetic association did not vary significantly even after multivariate association (p = 7.02 × 10 −15 in the unadjusted model; p = 3.35 × 10 −14 in the model adjusted for sex, age, and diabetes and p = 8.90 × 10 −14 , in the model adjusted for sex, age, diabetes, BMI, medications (including antihypertensive drugs, lipid lowering drugs, and insulin and oral antidiabetic medication), smoking, physical activity, and adherence to the Mediterranean diet. A previous GWAS in the Framingham study also showed a slight effect of the dietary adjustments in the SNP-PUFA associations [122]. Additional adjustment of the model containing all of these variables for more medications (including drug for pain and fever, anti-platelet drugs, tranquilizers-sedative-hypnotics, and vitamins/minerals), did not substantially change the statistical significance of the association between the FADS1-rs174547 polymorphism and serum omega-3 concentrations (p = 2.90 × 10 −13 ).…”
Section: Gwas For Serum Omega-3 Pufa (%) In This Populationmentioning
confidence: 74%
“…Some GWAS have considered dietary intake in adjustments carried out in the statistical analysis, indicating a modest influence [122]. However, to better understand dietary modulation, a gene*diet interaction analysis should be carried out.…”
Section: Discussionmentioning
confidence: 99%